Development of Tetracycline by AgO Nanoparticles and Studying its Activity on Antibiotic-Resistant Bacteria : Pengembangan Tetrasiklin dengan Nanopartikel AgO dan Mempelajari Aktivitasnya pada Bakteri yang Resisten terhadap Antibiotik - Wafaa Majeed; Hiba Shihab Ahmed; Zaineb Abd_Alkhalq Hamed (Academia Open, 2024)
General background: Antibiotic resistance in bacteria has become a critical global health issue, necessitating the development of new strategies to enhance antibiotic efficacy. Specific background: Nanoparticles, particularly silver nanoparticles (AgNPs), have emerged as potential enhancers of antibiotics due to their unique properties and interactions with bacterial cells. Knowledge gap: However, the combination of nanoparticles with existing antibiotics, such as tetracycline, and their impact on bacterial inhibition and safety has not been fully explored. Aims: This study aims to investigate the antibacterial activity of silver oxide nanoparticles (AgO NPs) combined with tetracycline (TCS) and evaluate their effectiveness against resistant bacterial strains. Results: AgO NPs were synthesized using a photodeposition method, yielding nanoparticles with an average diameter of 2.24 nm. The AgO NPs + TCS combination demonstrated superior antibacterial activity, with a minimum inhibitory concentration (MIC) of 16 μg/mL against Staphylococci and 32 μg/mL against Pseudomonas aeruginosa, significantly outperforming standard tetracycline. Hemolysis assays confirmed the safety of the synthesized compound at all concentrations. Novelty: Silver oxide nanoparticles and tetracycline exhibit a unique synergistic interaction, enhancing antimicrobial effects by increasing bacterial membrane permeability, facilitating greater antibiotic infiltration. Implications: These findings suggest that AgO NPs combined with tetracycline offer a promising solution to overcome bacterial resistance, providing a potent and safe alternative to conventional antibiotic treatments. Highlights: AgO NPs and tetracycline show enhanced antibacterial effects. More effective than standard tetracycline against resistant bacteria. Safe with no toxicity observed in hemolysis tests. Keywords: Antibiotic resistance, silver nanoparticles, tetracycline, photodeposition, antibacterial activity